KONSEP PENDIDIKAN ISLAM DAN PENGEMBANGAN KESADARAN LINGKUNGAN - Magfirotul Fatkha (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2022)
Development of awareness of the importance of the environment is a journey that must be pioneered for the sake of the survival of the next generation so that it is not threatened due to irresponsible human behavior today. Environmental education aims at introducing various values and explaining concepts to develop the ability of attitudes and skills needed to understand and appreciate the mutual relations between humans, culture, and the biophysical environment. This study aims to dig deeper about the development of environmental awareness in Islamic education. This study uses the literature study method by making a number of the results of the studies of previous researchers as the main data source. The results showed that the development of environmental awareness can be implemented through religious values with an environmental perspective in Islamic educational institutions. The religious climate in the environment in Islamic educational institutions can be realized through approaches: the creation of a religious education environment; the realization of worship facilities; the realization of the learning method by using the approach of religious values in every learning, especially religious values with an environmental perspective; dan the realization of the example of educators who have noble morals in particular having a concern for theenvironment.